P-100 Improvement in Quality of Life as a Predictor of Long-Term Remission in Crohn's Disease Patients Treated with Certolizumab Pegol. (March 2016) - Feagan, Brian; Schreiber, Stefan; Spearman, Marshall; Kosutic, Gordana; Hasan, Iram; Coarse, Jason; Sandborn, William
Abstract : Background: Exploratory analyses indicate rapid improvement in health-related quality of life following tumor necrosis factor (TNF) antagonist therapy for Crohn's disease (CD) may be associated with better outcomes. 1 We evaluated improvement in Inflammatory Bowel Disease Questionnaire (IBDQ) scores as a predictor of long-term remission in patients with CD who were treated with certolizumab pegol (CZP; a pegylated Fc-free TNF antagonist). Methods: Data from C87088 study (a 5-year open-label extension trial of CZP in patients with CD who participated in a 6-week placebo [PBO]-controlled induction study [C87085] of CZP versus PBO, 2 N = 403) were used for analysis. Outcomes considered to indicate rapid improvement were an increase in total IBDQ score of ≥32 points and/or IBDQ remission (≥170 points) at any time prior to and including week 0 of C87088. Loss of IBDQ remission was defined as scores <170 points. Kaplan-Meier estimates with log-rank tests were used to evaluate time to loss of remission by rapid IBDQ remission status. Results: Improvement in IBDQ scores of ≥32 points at or before week 0 of C87088 was present in 46.2% of patients treated with PBO and 53.0% of those treated with CZP; demographics at baseline were similar for the 2 treatment groups. The mean (SD) time to IBDQ remission was 110.8 (197.4) days for those treated with PBO and 88.5 (172.7) days for those treated with CZP during C87085. Patients with IBDQ remission at or before week 0 of C87088 (n = 179, 45%) had similar demographics and disease characteristics at baseline as those without rapid remission (n = 218, 55%), regardless of treatment. The median [95% confidence interval] time to loss of remission during the 5-year extension study was longer for patients with rapid IBDQ remission (1.1 [0.9–1.5] years) relative to those who without rapid remission (0.8 [0.5–1.3] years). Conclusions: These data suggest that patients who achieve improvement in IBDQ scores and/or IBDQ remission at or before week 0 of C87088 may have better outcomes over long-term treatment with CZP than those who do not achieve rapid improvement in quality of life.